Open Innovation - Latouche, Pascal (John Wiley & Sons, Incorporated, 2019)
The corporate start-up incubator is currently developing in large companies as an essential approach to open innovation. It faces a global system involving varied contexts, issues and actors. Its implementation is an art and to succeed the corporate incubator must become a real "interaction architect". Using testimonials and real case studies, the author takes a dive into the structural and social mysteries of corporate incubators. By analyzing the complex mechanisms of interactions, this book decrypts and reveals the keys to the success of these devices and to opening innovation in a broad sense. The concept of an "interaction architect" is related to the art of building fruitful interactions within human systems. Being aware that social systems exist is good, but knowing how to manage them is better.